Impact of Social Media on Students’ Academic Performance: A Quantitative Case Study of Kohat University of Science and Technology, Pakistan - Saiqa bibi; Shahzeb Anwar (`, 2025)
This study examines the impact of social media usage on students’ academic performance at Kohat University of Science and Technology (KUST), Pakistan. Recognizing the rapid expansion of digital platforms among youth, the research sought to assess whether excessive engagement with social media hinders students’ educational outcomes. Employing a quantitative research design, data were collected from a sample of 134 undergraduate and postgraduate students across multiple disciplines through a structured questionnaire. Statistical analysis revealed a significant negative relationship between time spent on social media and students’ academic performance, measured through self-reported GPA and study habits. The findings indicate that prolonged and unregulated use of platforms such as Facebook, Instagram, and TikTok contributes to distraction, reduced study efficiency, and declining grades. The study concludes that while social media provides opportunities for connectivity and informal learning, its misuse poses a serious challenge to students’ academic success at KUST. A key recommendation is the integration of awareness programs and digital literacy initiatives within the university, aimed at encouraging balanced and purposeful social media use. These findings have broader implications for higher education institutions in Pakistan, highlighting the need to address digital consumption patterns as part of student support and academic development strategies. Keywords: Social Media, Academic Performance, University Students, Digital Distraction, Pakistan